2007
DOI: 10.1007/s10820-006-9032-y
|View full text |Cite
|
Sign up to set email alerts
|

Prototype evaluation of transformation toughened blast resistant naval hull steels: Part II

Abstract: Application of a systems approach to computational materials design led to the theoretical design of a transformation toughened ultratough high-strength plate steel for blast-resistant naval hull applications. A first prototype alloy has achieved property goals motivated by projected naval hull applications requiring extreme fracture toughness (C v > 85 ft-lbs or 115 J corresponding to K Id ≥ 200 ksi.in 1/2 or 220 MPa.m 1/2 ) at strength levels of 150-180 ksi (1,030-1,240 MPa) yield strength in weldable, forma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
27
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 16 publications
6
27
0
Order By: Relevance
“…[1,2] BA160 is a low carbon martensitic steel additionally strengthened primarily by nanometersized Cu-rich precipitates and M 2 C precipitates (where M = Cr, Mo, and V). The yield strength of BA160 is 160 ksi (1104 MPa).…”
Section: To Meet the Rigorous Requirements For The Unitedmentioning
confidence: 99%
See 1 more Smart Citation
“…[1,2] BA160 is a low carbon martensitic steel additionally strengthened primarily by nanometersized Cu-rich precipitates and M 2 C precipitates (where M = Cr, Mo, and V). The yield strength of BA160 is 160 ksi (1104 MPa).…”
Section: To Meet the Rigorous Requirements For The Unitedmentioning
confidence: 99%
“…(1) In subcritical HAZ regions (SCHAZ; T P < A c1 ), no detectable transformation of ferrite to austenite occurs. (2) In the intercritical HAZ (ICHAZ), partial transformation of ferrite to austenite occurs because the peak temperature is between A c1 and A c3 . (3) In the fine-grained HAZ (FGHAZ), the samples are heated to a temperature slightly above the A c3 temperature, after complete austenitization.…”
Section: To Meet the Rigorous Requirements For The Unitedmentioning
confidence: 99%
“…17. High resolution microanalysis confirmed that the predicted strengthening and toughening dispersions were achieved, including the desired optimal austenite composition [87]. Continued development of variants of this steel by QuesTek has already demonstrated exceptional ballistic performance for fragment protection.…”
Section: High Strength and Toughness Steelsmentioning
confidence: 64%
“…With steadily improving accuracy of design models and their supporting fundamental databases, an important milestone has been the demonstration of a successful design within a single iteration of prototyping. Described in detail elsewhere [86,87], a weldable high strength plate steel for naval blast protection applications was designed to maintain the impact toughness of the Navy's current HSLA 100 steel out to [87] significantly higher strength levels. Adopting a tight carbon limit to promote high weldability, highly efficient strengthening was designed through a combination of copper precipitation and optimized alloy carbide precipitation.…”
Section: High Strength and Toughness Steelsmentioning
confidence: 99%
“…Cementite particles then become the prime fracture initiators. A goal in the computational design of blast-resistant steel [1] was therefore to eliminate cementite by controlled alloy-carbide precipitation which leads to finer dispersions by virtue of the need for substitutional solutes to diffuse [1,2]. The intended matrix would then be based on a secondary-hardened bainite and martensite mixture, containing dispersed austenite, the stability of which is designed to exploit transformation plasticity.…”
Section: Blast-resistant Steelmentioning
confidence: 99%